CD4 count remission hypothesis in patients with inflammatory bowel disease and human immunodeficiency virus infection: a systematic review of the literature - Skamnelos, Alexandros (Ann Gastroenterol, 2015)
BACKGROUND: Patients with inflammatory bowel disease (IBD) and human immunodeficiency virus (HIV) infection have shown controversial data concerning the remission hypothesis of IBD due to CD4 count depletion caused by HIV. The aim of our systematic review was to investigate the hypothesis whether low CD4 count due to HIV is related to IBD remission. METHODS: We systematically searched PubMed for studies reporting on HIV infection in IBD patients. We extracted characteristics of IBD and HIV disease course and CD4 counts. RESULTS: Thirteen papers (2 case-control studies, 2 case series, and 9 case reports) were eligible including 47 patients with IBD and HIV infection (43 male; 27 with Crohn’s disease, 19 with ulcerative colitis, and 1 with indeterminate colitis). The IBD diagnosis criteria were heterogeneous among studies. Remission was reported for patients with IBD and HIV infection in 5 studies, including 4 case-control or case series and 1 case report. Four of 5 studies with IBD cases reported remission related to the CD4 count remission hypothesis but only 2 of them explicitly reported the CD4 count cut-off point (500 cells/μL and 200 cells/mm(3) respectively). On the contrary, 7 case reports described an active IBD course or relapse even in patients under immunosuppression. CONCLUSIONS: Current literature cannot support or reject the CD4 count remission hypothesis in IBD patients with HIV infection. Prospective studies using uniform criteria on IBD and HIV disease course and CD4 counts are needed.